Tracing the P2P Botnets Behaviours via Hybrid Analysis Approach - Raihana Syahirah Abdullah, RS Abdullah; Mohd Faizal ABdollah, Faizal M.A.; Zul Azri Muhamad Noh, ZAM Noh (eurojournals, 2014)

(untitled)
P2P botnets has become central issue that threatens global network security. The unification of botnets and P2P technology make it more powerful and complicated to detect. P2P botnets generally known with abnormal traffic behaviours may highly impact the networks operation, network security and cause financial losses. In order to detect these P2P botnets, a highly-profile investigation on flow analysis is necessary. We consider hybrid analysis approach that integrate both static analysis and dynamic analysis approach. The hybrid analysis will be used in profiling the P2P behaviours and characteristics. Then, the findings of analysis results will contributes on P2P botnets behaviour pattern that will be used in constructing the general model of P2P botnets behaviour. Through the findings, this paper proposes a general P2P botnets behaviour model. The proposed model will be beneficial to further work on P2P botnets detection techniques.